2015
DOI: 10.1186/s13089-015-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Focused transesophageal echocardiography for emergency physicians—description and results from simulation training of a structured four-view examination

Abstract: BackgroundTransesophageal echocardiography (TEE) offers several advantages over transthoracic echocardiography (TTE). Despite these advantages, use of TEE by emergency physicians (EPs) remains rare, as no focused TEE protocol for emergency department (ED) use has been defined nor have methods of training been described.ObjectiveThis study aims to develop a focused TEE examination tailored for the ED and to evaluate TEE skill acquisition and retention by TEE-naïve EPs following a focused 4-h curriculum.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 26 publications
0
62
0
Order By: Relevance
“…These platforms are especially important to TEE-naïve since improves expertise, speed learning and comfort with TEE [65][66][67][68][69].…”
Section: Training and Competenciesmentioning
confidence: 99%
“…These platforms are especially important to TEE-naïve since improves expertise, speed learning and comfort with TEE [65][66][67][68][69].…”
Section: Training and Competenciesmentioning
confidence: 99%
“…Fifty-three of the 54 studies were determinate making it a reliable tool. Furthermore, 78% of the studies had diagnostic influence and impacted therapeutic decisions in 67% of TEEs.These studies demonstrate a much faster training curve [5,6] and greater clinical utility [4] than expected. Commonly, incorporation of TEE meets a great deal of resistance due to the cost of the TEE probe (estimated at $40,000 USD [4]), interdepartmental politics and lack of established training models [4].…”
mentioning
confidence: 99%
“…These trainees were then trained in advanced TEE and assessed at one, three and six months. This study found that the performance of at least 31 examinations over six months were required to reach competence in advanced TEE.In 2015, Arntfield, et al, expanded on the use of TEE as an additional form of basic point of care ultrasound in the emergency department [6]. This study trained a small group of emergency physicians experienced in TTE to perform a basic four view TEE [6].…”
mentioning
confidence: 99%
See 2 more Smart Citations